Risk perception, knowledge, prevention, information sources and efficacy beliefs related to Covid-19. (30th September 2020) - Genovese, C; Signorelli, C; Pavia, M; Icardi, G; Mistretta, A; Casuccio, A; Villari, P; Pellissero, G; Siliquini, R; Squeri, R
Abstract: Background: Sars-Cov-2 is one of the latest examples of an emerging infectious disease challenging the world and it is the third case, in just two decades, of "spillover". In light of the recent outbreak (Italy is in 2nd position), it is important to evaluate people risk perception and to support the Health Authority with effective communicative actions to avoid the spread of "infodemia"/alarmism. The aim of this study is a) to study levels of perceived threat, risk perception, severity and comparative vulnerability b) to compare risk perception with other communicable/not communicable diseases; c) provide information to increase awareness/ knowledge of the disease. Methods: We performed an Italian multicentre study from 11 February 2020 and it is still in progress. The subjects in study (general population, HCWs and university students) were enrolled through the administration of a standardized questionnaire based on Health Belief Model through CAPI and CAWI methods. The summary and inferential statistical analyses will be carried out using the R software. Results: We enrolled 2495 people from 11 February until 4 March 2020. All the respondents had heard of COVID19. Only 2% didn't know any symptoms and 3% answered to all the questions correctly (mean knowledge score of 13). 48% thought that he/she could acquired COVID 19 in the next 12 months and 70% stated that their concern of the disease was high(score5). Perceived capability to avoid it was rated as good/very good by 62%. The correct mask use (WHO) was reported by 64% of the sample and 47% stated all preventive actions (2% no one). Only 22% of the sample stated all actions to be taken in case of suspected acquisition of COVID19. Conclusions: Italy is facing an epidemic that could have the potential to affect the entire national health system. It's so important to implement public health activities and surveillance systems in order to limit the spread of the disease and bad/disinformation. Key messages: This study is the first to report on public perception of Sars-Cov-2 in all the Italy. The results indicated that the Italian population is aware of the outbreak and it is concerned about their risk. On the other hand, only half of the sample is aware about all preventive actions and not everybody knows all procedures to be taken in case of COVID 19 suspect.